Estimation of Tidal Stream Potential in the Iroise Sea from Velocity Observations by High Frequency Radars. (August 2015) - Thiébaut, Maxime; Sentchev, Alexei
Abstract: A year-long surface current velocity time series recorded by High Frequency radars (HFR) are used for assessing the hydrokinetic resources at a near-shore site in the Iroise sea. A combination of remotely sensed surface velocities and ADCP velocity profiles recorded in radar coverage zone allowed assessing the tidal current variability and power density variations in three dimensions. The analysis revealed two areas with high energy potential: the Fromveur Strait and the area NW of the Ushant Island where the kinetic power density in the surface layer attains 1.5kW/m2. The power available in the bottom layer is 3 times lower.